2017
DOI: 10.1097/icu.0000000000000369
|View full text |Cite
|
Sign up to set email alerts
|

Advancements of vitreoretinal surgical machines

Abstract: With recent advancements in vitreoretinal surgical machines, surgical incisions have become less traumatic and fluidics control has led to a more controlled posterior segment vitrectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 14 publications
0
12
0
5
Order By: Relevance
“…For this reason, three‐dimensional visualization instruments have recently been introduced in different surgical disciplines in which physicians routinely used endoscopic visualization devices or Galilean microscopes (GM) (Welcker et al 2012; Felisati et al 2013; Liang et al 2013; Ehlers et al 2014; Dutra‐Medeiros et al 2017; Martinez‐Toldos 2017; Ehlers et al 2018; Kita et al 2018; Maruyama et al 2018). The potential advantages of this new technology are very promising: higher quality of images, greater depth of focus, the possibility to integrate the images with other diagnostic devices, lower endo‐illumination intensity needed (in order to reduce the risk or retinal phototoxicity) and the ability to share all the details of the surgery in real time with other colleagues, thereby overcoming the limitations of traditional GM (Weinstock 2010; Eckardt & Paulo 2016; Adam et al 2017; Lin et al 2017; Williams 2017; Romano et al 2018; Talcott et al 2019). It is also important to be alert to any potential disadvantages, such as the time lapse between surgical interventions and their visualization, ergonomic details, costs and the learning curve required to use new technology efficiently (Williams 2017; Chhaya et al 2018; Romano et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, three‐dimensional visualization instruments have recently been introduced in different surgical disciplines in which physicians routinely used endoscopic visualization devices or Galilean microscopes (GM) (Welcker et al 2012; Felisati et al 2013; Liang et al 2013; Ehlers et al 2014; Dutra‐Medeiros et al 2017; Martinez‐Toldos 2017; Ehlers et al 2018; Kita et al 2018; Maruyama et al 2018). The potential advantages of this new technology are very promising: higher quality of images, greater depth of focus, the possibility to integrate the images with other diagnostic devices, lower endo‐illumination intensity needed (in order to reduce the risk or retinal phototoxicity) and the ability to share all the details of the surgery in real time with other colleagues, thereby overcoming the limitations of traditional GM (Weinstock 2010; Eckardt & Paulo 2016; Adam et al 2017; Lin et al 2017; Williams 2017; Romano et al 2018; Talcott et al 2019). It is also important to be alert to any potential disadvantages, such as the time lapse between surgical interventions and their visualization, ergonomic details, costs and the learning curve required to use new technology efficiently (Williams 2017; Chhaya et al 2018; Romano et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…He showed that with port biased open, the flow rate decreased with an increasing cut-rate for any given vacuum setting. This observation is different from ours as we used dual blade cutters in all our experiments whereas a single blade cutter was used in Abulon’s experiment; thus showing the superiority of dual blade cutters at maintaining a stable flow rate across various machine settings [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 70%
“…10 The idea of combining different sclerotomy sizes is not new and was possibly motivated by the fact that small-size high-speed cutters tend to produce less vitreoretinal traction and thus carry a lower risk of inducing retinal breaks while allowing vitreous removal with high efficacy. 14 The term "hybrid vitrectomy" was coined for the simultaneous use of sclerotomies of different diameters. This approach can utilize the strengths inherent to each technique while trying to minimize its known limitations.…”
Section: Discussionmentioning
confidence: 99%
“…13 In addition to these technological cornerstones, a further improvement came through the introduction of trocar systems that reduce the risk of entry site breaks. 1,14 An increased cutting speed as well as minimized tractional forces to the vitreal base and retinal periphery reduce the risk of postoperative retinal detachment despite shorter surgical times. 2,3 As smaller sclerotomy size leads to lower surgical trauma to the ocular surface, 15 efforts are underway to further reduce the size beyond 27G.…”
Section: Introductionmentioning
confidence: 99%